Hall effect in charged conducting ferroelectric domain walls - M. P. Campbell (Nature Portfolio, 2016)
Conduction in ferroelectric domain walls is now an established phenomenon, yet fundamental aspects of transport physics remain elusive. Here, Campbellet al. report the type, density and mobility of carriers in conducting domain walls in ytterbium manganite using nanoscale Hall effect measurements.